Pemberdayaan Lansia Tangguh Vokasional Melaui Pelatihan Keterampilan Merajut di Pondok Pesantren Al Muharrir Jlegongan Margodadi Seyegan Sleman Yogyakarta - Suji’ah, Uju; Hibana; Herawati, Tri Ratna; Surifah; Giyartiningrum, Eko; Prasojo, Eko; Pamungkas, Leo Dadyo (Kurnia Mengabdi: Jurnal Pengabdian kepada Masyarakat, 2025)
One aspect of elderly empowerment is vocational training, which involves developing skills and hobbies that can generate income or engage in productive activities such as knitting. Therefore, the goal of Community Service is to train knitting skills so that elderly women can utilize their free time by producing handicrafts. Wool yarn can be processed into tablecloths, coasters, key chains, tissue holders, and other crafts that can be useful for themselves and can be turned into profitable businesses. The activity is carried out in several stages, including preparation, implementation, evaluation of training results, and reporting. This activity is carried out in collaboration with Rizqun Minallah (RizMina), a community empowerment community specializing in skills and crafts. The training participants included 13 elderly women and administrators of the Al Moharrir Elderly Islamic Boarding School. Results: Participants were very enthusiastic about participating in the theory and practice of the knitting skills training. They strove to complete their knitting with enthusiasm. Despite difficulties, they continued to try until they produced the desired product that could be used for themselves, but not yet suitable for sale. The community service team and RizMina provided support to participants after the activity concluded.